2017
DOI: 10.1186/s12939-017-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Indigenous health research have impact? A systematic review of reviews

Abstract: BackgroundAboriginal and Torres Strait Islander Australians (hereafter respectfully Indigenous Australians) claim that they have been over-researched without corresponding research benefit. This claim raises two questions. The first, which has been covered to some extent in the literature, is about what type(s) of research are likely to achieve benefits for Indigenous people. The second is how researchers report the impact of their research for Indigenous people. This systematic review of Indigenous health rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 72 publications
(73 reference statements)
1
36
0
Order By: Relevance
“…Building trust between researchers and communities is an essential element of ethical research with Aboriginal people 14,17,20 and partnerships more generally 30,34 . Mistrust towards researchers can exist in Aboriginal communities because of past research that has provided little or no direct benefits to, or even harmed, the participating communities 33,35‐37 . Initial mistrust existed in rural Aboriginal communities in this study, but integrating processes and actions with direct benefit to the community helped build the trust in the partnerships and broader community.…”
Section: Discussionmentioning
confidence: 81%
“…Building trust between researchers and communities is an essential element of ethical research with Aboriginal people 14,17,20 and partnerships more generally 30,34 . Mistrust towards researchers can exist in Aboriginal communities because of past research that has provided little or no direct benefits to, or even harmed, the participating communities 33,35‐37 . Initial mistrust existed in rural Aboriginal communities in this study, but integrating processes and actions with direct benefit to the community helped build the trust in the partnerships and broader community.…”
Section: Discussionmentioning
confidence: 81%
“…There are a range of survey instruments available internationally to measure resilience for both the general population and youth ( 9 11 ). However, they are rarely or inconsistently used to inform decision-making in health and education services for Indigenous youth ( 12 ) for reasons that include: concerns about risk based questions and their potential impact on students; lack of resourcing for services to conduct intervention-based research; concerns over the capacity to respond to mental health issues raised by the instrument, and; concerns over the appropriateness and relevance of international instruments for utility with Indigenous Australian youth ( 13 ). The suitability of international instruments for use with Indigenous Australian youth is also linked to broader concerns of data sovereignty—the production, ownership, and use of Indigenous data—and the cultural appropriateness of using standard measures in Indigenous contexts ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a range of survey instruments available internationally to measure resilience and risk, our literature search, and workshops suggested that the instruments are rarely or inconsistently used to inform the decision making of education and health services (Kinchin et al, 2017). This might be because of a reluctance by education and health professionals to ask risk-based questions because of valid fears about students' vulnerability, such as we found in this study.…”
Section: Discussionmentioning
confidence: 79%